TINJAUAN FIQH MUAMALAH TERHADAP PEMANFAATAN TUMBUHAN SEBAGAI PAMBATEH TANAH - Sandra Eka Mulia; Eficandra Eficandra (Institut Agama Islam Negeri Batusangkar, 2022)
The main problem in this study is the analysis of the use of plants used as soil Pambateh according to Fiqh Muamalah (Case Study of Jorong Bukik, Nagari Tanjuang Bonai, North Lintau Buo District, Tanah Datar Regency). The purpose of this study was to fint out and explain what factors caused the collapse of plants that were used as soil Pambateh. To find out and explain how to resolve disputes over the use of plants used as land Pambateh. And to find out and esplain how fiqh muamalah reviews the status of ownership of plants used as land Pambateh in Jorong Bukik, Nagari Tanjuang Bonai, North Lintau Buo District, Tanah Datar Regency. The type of research that the author uses in this research is (field research) with a qualitative approach. Primary data sources in this study consisted of three plant owners, three parties who used plants, two Ninik Mamak, two Alim Ulama and Kerapatan Adat Nagari (KAN). The results showed that the factor of the collapse of natural factors in the form of prolonged heavy rains, the presence of livestock that stepped on the soil, and many people who threw garbage on the land. With the collapse of plants that are used as land Pambateh, there is a dispute between the owner of the plant and the party who used the plant. The way to resolve the dispute is through deliberation and consensus.